2020
DOI: 10.18549/pharmpract.2020.2.1847
|View full text |Cite
|
Sign up to set email alerts
|

Cost of hospitalisation and length of stay due to hypoglycaemia in patients with diabetes mellitus: a cross-sectional study

Abstract: Objective: This study aims to estimate the length of stay and hospitalisation cost of hypoglycaemia, and to identify determinants of variation in the length of stay and hospitalisation cost among individual patients with type 1 or 2 diabetes mellitus.  Methods: A cross-sectional study was conducted using inpatients records for patients with diabetes mellitus who had been hospitalised due to hypoglycaemic events in two private hospitals in Amman, Jordan between January 2009 and May 2017. All hospitalisati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 38 publications
1
12
0
Order By: Relevance
“… 7 Frequent hospitalisation that could lead to financial loss, job loss, diminished interaction with family, psychological effects, and other issues is an example of the effects of DM on QoL. 8 However, DM is not the only factor that can affect the QoL of a diabetic patient. According to the World Health Organization (WHO), QoL is defined as “an individual’s perceptions of their position in life in the context of the culture and value systems in which they live, and in relation to their goals, expectations, standards, and concerns.…”
Section: Introductionmentioning
confidence: 99%
“… 7 Frequent hospitalisation that could lead to financial loss, job loss, diminished interaction with family, psychological effects, and other issues is an example of the effects of DM on QoL. 8 However, DM is not the only factor that can affect the QoL of a diabetic patient. According to the World Health Organization (WHO), QoL is defined as “an individual’s perceptions of their position in life in the context of the culture and value systems in which they live, and in relation to their goals, expectations, standards, and concerns.…”
Section: Introductionmentioning
confidence: 99%
“…Similar results were obtained in the study reported by Naser et al for LOS, but opposite results were reported for hospitalisation costs. 35 During the study, it was observed that fasting blood sugar (FBS) 261-290 mg/dL and >290 mg/dL (P = .012). The mean difference is considered significant at the 0.03 level.…”
Section: Re Sultsmentioning
confidence: 93%
“…In India, approximately 73 million people living with diabetes, and another 37 million with prediabetes, while nearly 47% of the diabetes cases are undiagnosed 46. Several studies have shown that age, poor education, family history of diabetes, physical inactivity and obesity were risk factors of DM coexisting HTN 33,35,[47][48][49][50][51][52]. The Ministry of Health, Government of India, has initiated an insurance scheme 'World's biggest health reforms: Ayushman Bharat-National Health Protection Scheme' in 2018 claiming benefited to around 500 million citizens of the country 53,54.…”
mentioning
confidence: 99%
“…According to the World Health Organization (WHO), Saudi Arabia is ranked second among the highest percentages of diabetes worldwide, with more than 7 million patients with diabetes reported in 2017 [2], with the prevalence being estimated to be around 14% [1]. Patients with diabetes are usually treated with pharmacological treatment to control their blood sugar levels, and this put them at higher risk of developing some life-threatening and costly complications such as hypoglycaemia [3][4][5].…”
Section: Introductionmentioning
confidence: 99%